The relationship of oocyte diameter with ovarian development in the sea cucumber Holothuria scabra (P. Echinodermata Cl. Holothuroidea). - Cordero, Ethel Deypalubos (1994.)
Forty two prepared histological slides of female Holothuria scabra individuals collected at Taklong Island from July 1984 to June 1985 were investigated. Oocyte diameters of the individuals were measured to assess the relationship of oocyte diameter with ovarian development in the species., Measured oocytes with diameters measuring less than thirty microns were considered as immature. Oocytes were considered as maturing when their measured diameters were greater than thirty microns but less than sixty microns. Mature oocytes had diameters measuring greater than sixty microns. A relative frequency distribution polygon was constructed to determine the dominant size classes of oocytes in each maturity stages. The mean oocyte diameters of the individuals were correlated with gonadosomatic index ( GSI ), lenghts and weights using correlation test r. A relative size frequency distribution of oocyte diameter on a monthly basis was also constructed to visualize the monthly oocyte diameter profile of the species. (p)This study showed that immature oocytes have diameters ranging from 6.5 microns to 29.25 microns. These oocytes were dominant in sexual maturity stages from I (resting) and II (recovery). Maturing oocytes have diameters ranging from 32.5 - 58.5 microns and are predominantly present in sexual maturity stage III. Mature oocytes have diameters ranging from 61.75-110.5 microns. These oocytes dominate sexual maturity stages IV (mature) and V (shedding). (p)GSI, body lengths and body weights of the individuals are positively correlated with the mean oocyte diameter of the species H. scabra. However, the strength of the linear relationships existing between the variables are not strong, having a correlation coefficient r less than 0.70. Mature oocytes are dominantly present on the months of October to November and January to April indicating that the species H. scabra spawns during these months. On the other hand, immature oocytes are most frequent on the months of December and May.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Sea Cucumber; Holothuria scabra